Isolation and identification of novel selective antitumor constituents, sidrin and sidroside, from Zizyphus spina-christi - Mahmoud A.H. Mostafa; Hani M.J. Khojah; Tomihisa Ohta (Elsevier, 2023)
Background: The leaves of Zizyphus spina-christi (L.) Willd contain several compounds exhibiting different pharmacologic activities. However, studies on the cytotoxic activity of these compounds are limited. Objectives: We aimed to investigate and isolate cytotoxic compounds with selective antitumor effects from the leaves of Z. spina-christi using bioassay-guided fractionation of methanol extract. Methods: Powdered, dried leaves were subjected to methanol extraction and fractionated using n-hexane, chloroform, ethyl acetate, and n-butanol. Fractions with positive cytotoxicity against HeLa and THP-1 cell lines were further fractionated and eluted using various concentrations of organic solvents. Active compounds were isolated using different chromatographic methods and their chemical structures were determined using extensive spectroscopic methods, such as 1D NMR (1H NMR, 13C NMR, and DEPT), 2D NMR (COSY, HMBC, and HMQC), HRFAB-MS, and IR. Furthermore, the cytotoxic effects of the isolated compounds were evaluated against 62 tumor cell lines (including HeLa and THP-1) in addition to normal bone marrow cells. Results: The chloroform and aqueous methanol fractions of the leaves showed cytotoxic activity. Two compounds were successfully isolated and named "sidrin" (13-β-hydroxy-lup-20(30)-ene-2,3-β-epoxy-28-carboxylate) and "sidroside" (3-O-β-D-glucopyranosyl-(1-3)-α-L-arabinopyranosyl-jujubogenin-20-O-α-L-rhamnopyranoside). Sidrin exhibited cytotoxic activity against the human leukemia (Hl-60, RPMI-8226), lung cancer (A549, EKVX), breast cancer (BT-549, MDA-MB-231/ATCC), colon cancer (KM12), melanoma (M14, SK-MEL-5), and central nervous system (CNS) cancer (SF-295) cell lines, and selectivity was observed against the Hl-60, EKVX, BT-549, KM12, and SF-295 cell lines. In addition, sidrin was more active than sidroside and doxorubicin against the Hl-60 and EKVX cell lines. In contrast, sidrin had a similar effect to doxorubicin against the BT-549 and renal cancer (UO-31) cell lines. Sidroside was more selective against the leukemia (CCRF-CEM, MOLT-4), lung cancer (HOP-92, NCI-H322M), breast cancer (MDA-MB-468), melanoma (LOX IMVI), CNS cancer (SNB-19), ovarian cancer (OVCAR-8), renal cancer (UO-31, RXF 393), and prostate cancer (PC-3) cell lines. Both compounds exhibited similar activity against the breast cancer (MDA-MB-231, T-47D), colon cancer (HCC-2998, HCT-116), ovarian cancer (OVCAR-3), renal cancer (UO-31, 786-0, and SN 12C) cell lines. Normal bone marrow cells were unaffected at the same concentrations of sidrin and sidroside applied to tumor cells. Conclusions: These results suggest tumor-selective cytotoxicity of sidrin and sidroside.